The Improvements, Strategies And Benefits Of E- Business Of Grab Company In Lampung, Indonesia - Fitria -; Izzati Binti Mat Nor; Siti Nurliyana Binti Abdul Malik (Prosiding International conference on Information Technology and Business (ICITB), 2019)
E-business (electronic business) is the conduct of business processes on the internet. E-business processes include buying and selling products, supplies and services; servicing customers; processing payments; managing production control;collaborating with business partners; sharing information; running automated employee services. The purpose of this research is to study the improvement of e-business of Grab. The interest group for this research is the user of Grab application involving 101 respondents in Lampung. Lampung is a province of Indonesia. It is located on the southern tip of the island of Sumatra. This research is non-experimental study with analysis study. The objectives of this research are to study the improvement of e- business of Grab, to study the e-business strategies of Grab and to know the benefits of Grab for drivers and users. The result of this research is there’s a lot of improvement of e-business in grab application and services. This means that the benefits and strategies provided by Grab have significant influence to its improvement.Keywords: e- business, servicing customers, sharing information